TREATMENT OF COLORECTAL CANCER COMPLICATED BY INTESTINAL OBSTRUCTION USING THE METHOD OF «FAST-TRACK» RECOVERY - V. L. Denisenko; Yu. M. Gain (Вестник хирургии имени И.И. Грекова)
A medical trend which is currently gaining strength includes the complex treatment based on the concept of «fast-track» recovery in oncology. An application of modern high-tech approaches allowed minimizing the terms of treatment, shortening economic costs and getting the highest final results. It provides a high quality treatment. Given method could exclude an interim treatment stages, sufficiently reduces terms of general treatment and rehabilitation of patients and could succeed in high quality of life for the patients in short- and long-term period. The authors present the results of successful clinical surgery of 78 patients using this method in public health.